Stock Investment Decision On Generation Z In Makassar City: The Role Of Fear Of Missing Out, Loss Aversion And Financial Literacy - Rika Dwi Ayu Parmitasari; Eka Indriyani MS; Noval (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
Stock investments have shown an increasing trend in recent years, primarily driven by Generation Z, who grow up in the digital era with easy access to investment information through social media. This study aims to examine the influence of fear of missing out and loss aversion on stock investment decisions, as well as the moderating role of financial literacy among Generation Z in Makassar City. The research employs a quantitative associative approach, involving 150 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.0 software. The results of the study show that FOMO and loss aversion have a positive and significant influence on stock investment decisions. But the role of FOMO and loss aversion on stock investment decision cannot be moderated by financial literacy. This finding highlights that psychological biases such as FOMO and loss aversion greatly influence Generation Z's stock investment decisions regardless of their financial literacy levels, emphasizing the importance of enhancing financial education by considering psychological factors.